Pendampingan Industri Halal dalam Menumbuhkembangkan Usaha Mikro Melalui Ekonomi Kreatif - Astuti, Ristina Wahyu; Zihab, Zihab; Solatiyah, Baiq; Febrian, Dodi; Saripudin, Saripudin; Hernawati, Hernawati (Widya Balina, 2021)
Efforts to increase economic growth in Indonesia, the discourse that is often discussed is the use of the creative economy concept. In connection with the government's efforts to realize creative economic development and create halal products, the position of the government in increasing MSMEs is urgently needed. The purpose of this community service is to provide training on the latest insights to all parties involved in developing micro-enterprises through the creative economy. The method of implementing the activity consists of several stages. In the preparatory stage the team conducted a location survey, strengthening and determining target locations, and preparing socialization materials. In addition, participants participated in assistance in making halal products. The implementation stage of the program is in the form of lectures or outreach, tutorial activities, discussions and MSME training assistance. The material presented in the socialization is in the form of an introduction to the production process of halal products and provides direction in making halal labels. The results and outputs of the activities after the socialization was carried out, namely first, introducing the production process for halal products to the public, in this case the socialization team provided an understanding of how important the distribution of industrial potential is through the creative economy. Second, provide assistance in the form of making halal labels where at this stage the socialization team provides an understanding that in Islam products cannot contain harmful ingredients because they will have a negative impact on consumers and society.